Exercise during pregnancy increases hippocampal brain-derived neurotrophic factor mRNA expression and spatial learning in neonatal rat pup - Panaree Parnpiansil (2018)
Physical activities for a few days can increase brain-derived neurotrophic factor (BDNF) mRNA in rat hippocampus. To investigate the influence of maternal exercise during pregnancy on rat pup hippocampal BDNF mRNA, we studied its expression by a semi-quantitative RT-PCR method after young pregnant rats were exercised on a motor driven treadmill. Pups of exercised mothers had significantly increased hippocampal BDNF mRNA expression compared to the control rat pups at birth (on postnatal day 0) (P<0.001). In contrast, hippocampal BDNF mRNA expression in pups of exercised mothers decreased significantly on postnatal day 28 (P<0.002). Spatial learning of rat pups was examined by multiple T maze training for 7 consecutive days between postnatal days 40 and 47. Pups of exercised mothers showed a significant increase in spatial learning ability as demonstrated by significant decreases in total time from starting to target and total number of errors as compared to age-matched control pups during the first 4 days of 7 consecutive days on multiple T maze training (P<0.05). Thus, physical exercise during gestation in pregnant mothers can increase hippocampal BDNF mRNA expression of postnatal pups and result in an improvement in spatial learning in pups from exercised dams. © 2003 Published by Elsevier Ireland Ltd.